Determination of Quercetin Content in Aqueous and Ethanol Extracts of Ndusuk Leaves (Melastoma malabathricum L.) Based on UV-Vis Spectrophotometric Analysis - Damang, Yulien Brigita; Dean, Muhajirin; Purnasari, Cahyani; Neolaka, Yantus A. B. (Jurnal Biologi Tropis, 2026)
Ndusuk leaf (Melastoma malabathricum L.) is a plant containing flavonoid compounds, including quercetin, which has potential as an antioxidant, antibacterial, and antidiarrheal agent. Different types of solvents and extraction methods may affect the quercetin content obtained. This study aimed to determine and compare the quercetin content in aqueous and 95% ethanol extracts of Ndusuk leaves using UV-Vis spectrophotometry. This was a laboratory experimental study. Ndusuk leaf simplicia was extracted using the infusion method with water as the solvent and the maceration method with 95% ethanol. Quercetin content was determined using a UV-Vis spectrophotometer at a maximum wavelength of 361 nm. A quercetin standard curve was prepared at concentrations ranging from 4–12 ppm, yielding a linear regression equation of y = 0.0453x + 0.2356 with R² = 0.9942. The yields of aqueous and 95% ethanol extracts were 6.12% and 10.17%, respectively. The quercetin content in the aqueous extract was 0.84 ± 0.04 mg/g, while in the 95% ethanol extract it was 16.27 ± 0.15 mg/g. The 95% ethanol extract demonstrated significantly higher quercetin content compared to the aqueous extract. The use of 95% ethanol with the maceration method was more effective in extracting quercetin from Ndusuk leaves compared to aqueous extraction using the infusion method.